Effects of NPK fertilizer on the physiological attributes of yellow passion fruit seeds - Liuz, Rueben; Inacio, Sergio; Ambrosio, Paulo (Global Journal of Food and Agribusiness Management, 2017)
Brazil is the largest producer of passion fruit, having the Northeast region as the main producing region, where orchards are formed almost exclusively from seed. This work aimed to evaluate the influence of different qualities of water and four levels of liquid manure applied to the soil in the absence and presence of mineral NPK fertiliser on the physiological attributes of yellow passion fruit seeds. The seeds were produced in a field experiment conducted in Jaçanã county, Rio Grande do Norte State-Brazil and seed quality was assessed in the Laboratory of Seed Analysis (LSA) from Agrarian Sciences Centre of Federal University of Paraíba in Areia County, Paraiba State, Brazil. In the laboratory, the experimental design was completely randomised with 16 treatments in four repetitions. The bovine biofertiliser inhibited the seed quality obtained for plants irrigated with non-saline water, but increased the viability of seeds in plants irrigated with saline water. Characteristics evaluated were the first count of normal seedlings, and speed index germination (SIG, dry matter weight of roots and shoot). The mineral fertilisation of the soil with NPK increased the seed viabilityin plants irrigated with both non-saline and saline waters